PENGARUH FAKTOR-FAKTOR HEDONIC PRODUCT DAN SELF-EXPRESSIVE BRAND TERHADAP WILLINGNESS TO PAY A PREMIUM DENGAN BRAND LOVE PADA TOKO RITEL ZARA - Olivia Melisa Hermanto (Jurnal Strategi Pemasaran, 2019)
This opens up opportunities for foreign fashion businesses to enter Indonesia. In the world of fashion industry its products are made to express themselves. There is also an emotional side to using the product. These two things are important to build a love for these fashion products. This study intend to analyze the influence of hedonic factors and self-expression on the love of fashion brands. Zara was taken as the context of this study because the enthusiasm and love of its consumers is still stable despite the emergence of other brands.